1989
DOI: 10.1002/etc.5620081203
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses in aquatic animals: A review of determinants of oxidative stress

Abstract: The study of biochemical responses in aquatic animals comprises a vigorous area of inquiry within ecotoxicology for a number of reasons, including the perceived need for basic research in the field, the desire for highly sensitive biomarkers useful for biomonitoring and the particular concern for elevated rates of neoplasia observed in some aquatic systems. In this paper, an approach only recently investigated by aquatic toxicologists will be described and reviewed in detail. This approach is based on theories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(108 citation statements)
references
References 134 publications
4
101
0
Order By: Relevance
“…Our results are in agreement with those of SaintDenis et al (1998) on earthworm species Eisenia fetida, wherein catalase activity increased with age, and also in Arenicola, where CAT activity is higher in older compared to younger lugworms (Buchner et al 1996). Previous studies by Di Giulio et al (1989) indicated that CAT activity could be induced under conditions of oxidative stress. However, the CAT activity is altered by a number of other conditions, including changing nutritional status or oxygen status (Livingstone et al 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with those of SaintDenis et al (1998) on earthworm species Eisenia fetida, wherein catalase activity increased with age, and also in Arenicola, where CAT activity is higher in older compared to younger lugworms (Buchner et al 1996). Previous studies by Di Giulio et al (1989) indicated that CAT activity could be induced under conditions of oxidative stress. However, the CAT activity is altered by a number of other conditions, including changing nutritional status or oxygen status (Livingstone et al 1992).…”
Section: Discussionsupporting
confidence: 93%
“…In this context, cytochrome P450-dependent monooxygenase induction, measured as ethoxyresorufin O-deethylase (EROD) activity, has been widely used as a sensitive indicator of exposure to environmental contaminants (Addison et al, 1994;Martel et al, 1994;Pacheco and Santos, 1999). The activation of certain xenobiotics results in the production of potentially damaging oxyradicals, which react with many biological molecules including DNA (Di Guilio et al, 1989). Thus, DNA integrity can be affected.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation is essentially a toxic response to oxidative damage to cellular and tissue components (Di Giulio et al 1989). Increased ROS generation in tissues leads to the oxidation damage to polyunsaturated lipids (lipid peroxidation), proteins and DNA (Storey 1996).…”
Section: Discussionmentioning
confidence: 99%